Consumer attitude and preference in the Islamic mortgage sector: a study of Malaysian consumers - Amin, Hanudin; Abdul Rahman, Abdul Rahim; Abdul Razak, Dzuljastri; Hamid, Rizal (Emerald Group Publishing Ltd., 2017)
The purpose of this study is to investigate the effects of service quality, product choice and Islamic debt policy on consumer attitude within the context of Islamic mortgage sector in Malaysia. The present study also examines the effect of attitudinal-behaviour on consumer preference towards preference of Islamic mortgage selection